Extracorporeal Membrane Oxygenation in Acute Myocardial Infarction Complicated by Cardiogenic Shock - I. A. Kornilov; I. O. Grazhdankin; D. A., Redkin; M. N. Deryagin; S. M. Efremov; V. V. Lomivorotov (Общая реаниматология)
Cardiogenic shock is one of the main causes of death in patients with acute myocardial infarction with the mortality rates being as high as 60—80%. Extracorporeal membrane oxygenation (ECMO) is a life-saving technique in patients with cardiogenic shock. Subjects and methods. Veno-arterial ECMO was connected and the coronary arteries were stented in a 53-year-old female patient with acute myocardial infarction complicated by severe cardiogenic shock refractory to drug therapy and intra-aortic counterpulsation (IACP). ECMO was maintained at a volumetric perfusion rate of 4.5 l/min (2.5 l/min/m2). The duration of ECMO was 138.5 hours (5.8 days); that of IACP was 9 days. In the first 24 hours, there were no ECMO-related complications apart from mild bleeding from the site of cannula insertion. The patient stayed in the intensive care unit 12 days. Results. IACP is used to treat cardiogenic shock, but it is ineffective in severe cardiogenic shock. ECMO is one of the possible options for maintaining life and for stabilizing the condition. Current ECMO systems may be employed for urgent peripheral connection and coronary artery intervention. ECMO may be used for resuscitation and temporary life support, which permits as high as 50—75% of patients with refractory cardiogenic shock to be saved. Conclusion: emergency coronary stenting with ECMO support is the technique of choice for the treatment of acute myocardial infarction complicated by severe cardiogenic shock. Key words: extracorporeal membrane oxygenation, cardiogenic shock, coronary artery stenting.